Different responses of two maize cultivars to Spodoptera frugiperda (Lepidoptera: Noctuidae) larvae infestation provide insights into their differences in resistance - Yang, Jinwen; Ma, Changlu; Jia, Ru; Zhang, Haiyan; Zhao, Yanming; Yue, Haiwang; Li, Heqin; Jiang, Xuwen (Frontiers in Plant Science, 2023)
Spodoptera frugiperda (Lepidoptera: Noctuidae), a pest with an amazing appetite, damages many crops and causes great losses, especially maize. Understanding the differences in different maize cultivars responses to S. frugiperda infestation is very important for revealing the mechanisms involved in the resistance of maize plants to S. frugiperda. Here, comparative analysis of two maize cultivars, the common cultivar ‘ZD958’ and the sweet cultivar ‘JG218’ were used to investigate their physico-biochemical responses to S. frugiperda infestation by a pot experiment. The results showed that the enzymatic and non-enzymatic defense responses of maize seedlings were rapidly induced by S. frugiperda. Frist, the hydrogen peroxide (H2O2) and malondialdehyde (MDA) contents of maize leaves-infested were significantly increased and then decreased to the level of the control. Furthermore, compared to the control leaves, the puncture force values, the total phenolics, total flavonoids and 2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one (DIMBOA) contents of leaves-infested were significantly increased within a certain time; the superoxide dismutase (SOD) and peroxidase (POD) activities of leaves-infested were significantly increased in a certain period of time, while the catalase (CAT) activities decreased significantly and then increased to the control level; the jasmonic acid (JA) levels of leaves-infested were significantly improved, whereas salicylic acid (SA) and abscisic acid (ABA) levels changed less; signaling genes associated with phytohormones and defensive substances including PAL4, CHS6, BX12, LOX1 and NCED9 were significantly induced at certain time points, especially LOX1. Most of these parameters changed greater in JG218 than in ZD958. Moreover, larvae bioassay showed that S. frugiperda larvae weighed more on JG218 leaves than that on ZD958 leaves. These results suggested that JG218 was more susceptible to S. frugiperda than ZD958. Our findings will make it easier to develop strategies for controlling S. frugiperda for sustainable maize production and breed new maize cultivars with increased resistance to herbivores.